PERBANDINGAN ANTARA PEMBERIAN ANTIBIOTIKA PROFILAKSIS PADA SEKSIO SESAR SESUAI ALUR KLINIS RSUP DR SARDJITO DENGAN ANTIBIOTIKA DOSIS MULTIPEL TERHADAP KEJADIAN INFEKSI LUKA OPERASI - Ardian Rahmansyah; Mohammad Hakimi; Rukmono Siswishanto (JURNAL KESEHATAN REPRODUKSI, 2016)
Background: Clinical pathway recommend the use of short-term prophylaxis antibiotics for cesarean section. Long-term antibiotics or multiple doses was found in clinical practice. There are differences in the mode of administration and the number of doses administered at sardjito hospital.Objective: To determine the effectiveness of short-term antibiotic prophylaxis in cesarean section appropriate to clinical pathway in the prevention of surgical site infection (ssi), the incidence of fever, dysuria events, length of stay.Method: The study used randomized clinical trial. The study subjects who underwent cesarean section and meet the inclusion and exclusion criteria in the period July 2013 to January 2014 divided into an intervention group (n = 52) who received ampicillin 2 gram pre and post-cesarean section, and a control group (n = 54) who received ampicillin 2 gram pre cesarean section and 1 gram every 8 hours for 6 times. Observed on days 3 and 10 post-cesarean section. The primary outcomes assessed were the incidence of surgical wound infection based on the criteria of surgical site infection from Centers for Disease Controland Prevention. Secondary outcomes assessed were the incidence of fever, dysuria events, length of stay. Homogeneity analysis were conducted on subject. Outcome analysis performed bivariate with t test and chi squared test.Results and Discussion : A total of 106 subjects can be analyzed. SSI events in the intervention group at day 3 was 3.8% (n = 52) and control group was 1.84% (n = 54) with p>0.05 RR 2.077 (95% CI 0.194 to 22.219). SSI on day 10 of 7.7% (n = 52) in the intervention group versus 9.3% (n = 54) in controls with p<0.05 RR 0.831 (CI 95%, 0.236 to 2.924). Fever events on day 3 by 5.8% in the intervention group versus 3.7% incontrols with p>0.05 RR 1.558 (95% CI 0.271 to 8.948) and on day 10 was 3.8% versus 3.7 % with p>0.05 RR 1.038 (95% CI 0.152 to 7.102). Dysuria not found on day 3 and but on 10 found 5.8% in the intervention group versus 11.1% with p>0.05 RR 0.519 (IK95% 0.137 to 1.968). Length of stay after cesarean section for 3.21 ± 0.412 days in the intervention group and 3.26 ± 0.442 days in the control group with p>0.05 (95% CI -0.213 - 0.117).Conclusion: There is no significant difference in the incidence of surgical wound infections, the incidence of fever, dysuria, length of stay between short-term prophylaxis antibiotics ampicillin appropriate to clinical pathway and long-term or multiple doses prophylaxis antibiotics. Short term antibiotics prophylaxis are more efficiently with the same effectiveness in preventing outcomes research.Keywords: prophylaxis antibiotics, ampicillin, short term regimen, long term regimen, cesarean section, surgical site infection.